Bilateral Femoral Agenesis in 3-Month-Old Baby: : A Case Report - Foris, Emiliana Susanti; Mario Realino Nara,; Defranky Theodorus, (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2022)
Background Bilateral congenital femoral agenesis is a rare congenital anomaly. To the best of our knowledge, only three cases of simple congenital anomaly, three cases associated with femoral facial syndrome, have been reported. We describe a simple form of bilateral femoral agenesis observed in 3-month-old female baby without femoral facial syndrome and non-diabetic mother. Objective We report this case because it is a rare case and needs proper evaluation and management. The majority of cases, however, are sporadic, and therefore, the parents may be reassured that the risk of further offspring being affected is negligible. Case A 3-month-old female baby present with a complaint of short stature. The baby was born full term spontaneous labor, 2570 gram vigorous and started to cry immediately after birth. The mother has no history of diabetes, cigarette smoking, and exposure teratogens. The parents were not related by blood. X-ray examination showed bilateral agenesis of femur, normal tibia and fibula, proximal of cruris in lateral of acetabula. Conclusion Bilateral congenital femoral agenesis is a rare congenital anomaly. Although commonly associated with maternal diabetes mellitus, most cases have no known cause. Keywords: femoral agenesis, congenital deformity